Beyond words. Elin Skaar, Eric Wiebelhaus-Brahm, Jemima García-Godos. - Skaar, Elin; Wiebelhaus-Brahm, Eric; García-Godos, Jemima (Series on transitional justice ;, 2022)
Based on fieldwork that is unprecedented in scope, this two-volume project provides the first systematic study of the formulation and implementation of the recommendations of 13 Latin American truth commissions. Beyond Words Vol. I examines the variations in truth commission recommendations across 13 Latin American cases. Insights are provided regarding how the internal dynamics of truth commissions, as well as the political, social and economic context in which they operate, influence how recommendations are formulated. The authors then explore how the nature of these recommendations themselves, along with the aforementioned factors, influence which recommendations are actually implemented. The conclusion considers the findings' relevance for the crafting of future truth commission recommendations and reflects upon how the formulation and implementation of these recommendations shape the impact of truth commissions on societies emerging from periods of violence and repression.